Representasi Identitas Budaya dalam Cerita Rakyat Nusantara: Kajian Strukturalisme Levi-Strauss - Hendri Jihadul Barkah; Febri Desman (Pascasarjana Institut Seni Indonesia Padang Panjang, 2025)
Folktales, as part of the rich oral literary tradition of the Indonesian archipelago, play a significant role in shaping and representing the cultural identity of a society. This study aims to examine the narrative structures within Indonesian folktales using Claude Lévi-Strauss’s structuralist approach, which focuses on binary oppositions and the logical relationships between story elements. The method employed is qualitative-descriptive, utilizing narrative text analysis on five folktales from various regions in Indonesia, such as Malin Kundang (West Sumatra), Timun Mas (Java), The Legend of Lake Toba (North Sumatra), The Crying Stone (Kalimantan), and Sangkuriang (West Java). The findings reveal that beneath the variety of stories and geographical settings, there are recurring structural patterns, such as conflicts between child and parent, human and nature, or good and evil. These patterns reflect cultural values deeply held by the storytelling communities, such as respect for parents, moral consequences, and a spiritual relationship with nature. By mapping the structures within these folktales, the study finds that Indonesian folktales do not merely deliver entertainment or moral lessons, but also serve as symbolic representations of collective cultural identity. This study is expected to enrich the understanding of Indonesia’s oral cultural heritage and open pathways for cross-cultural interpretation through a structuralist lens.